FAKTOR-FAKTOR PENYEBAB DIARE PADA TODDLER DI PUSKESMAS KAMPAR KECAMATAN KAMPAR KABUPATEN KAMPAR - Andalia Roza; Putri Wulan Dini; Nurhafizah Nurhafizah (LPPM Universitas Abdurrab, 2022)
, Diarrhea is a condition of a person defecate (BAB) with the condidtency of soft or liquid can even be water just more frequent urination frequency serinh usually 3 times or more in one day. This study aims to determine the factorscausing diarrhea in toddler in kampar clinics and know the faktor associated with the incidence of diarrhea in health centers kampar. Metodologi: the disign used in this research is descriptive research type, with correlation research design, population in this research is all parents who have toddler who treatment at puskesmas kampar with amount of 40 toddler, sampling technique in this research by using technique of non probability sampling technique with total sampling samples. Data collection by fillinf out the questionnaire. The result of statistical test of factors related to environmental test of factors with diarrhea occurrence (p= 0,05), maternal sosciodemographic factor of education with diarrhea occurence (p= 0,517) maternal sosciodemographic factor with diarrhea occurrence (p= 0,897), sosciodemographic factor of occupation with diarrhea (p= 0,05), behavioral faktor with diarrhea occurrence (p= 0,512). It’s expected that parents can minimize the factors causing diarrhea that occurs in toddler, by maintaining the evironment and performing habits of life behavior.